Growth and production of secondary metabolites in the callus of Bima Brebes shallot varieties - NOOR AINI HABIBAH; ARI YUNIASTUTI; R. SUSANTI; LISDIANA LISDIANA; DEWI MUSTIKANINGTYAS; ANANDA LUTFIAH; SISKA NA'ILIL AULIA; TAQQIYA RABBANI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Habibah NA, Yuniastuti A, Susanti R, Lisdiana, Mustikaningtyas D, Lutfiah A, Aulia SN, Rabbani T. 2024. Growth and production of secondary metabolites in the callus of Bima Brebes shallot varieties. Biodiversitas 25: 2811-2820. Shallots contain bioactive compounds that can be produced through callus culture. This study investigates the effects of growth regulators 2,4-D, picloram, and kinetin on the growth and production of secondary metabolites in shallot bulb callus. A Complete Randomized Design (CRD) with two factors was used in the experiment. The first factor was the concentrations of 2,4-D (0, 1, 2, and 3 ppm) and picloram (0, 1, 2, and 3 ppm). The second factor was kinetin concentrations (0, 0.25, and 0.5 ppm). The parameters evaluated were callus fresh weight, callus dry weight, percentage of callus formation, callus induction time, callus morphology, phytochemical components, and antioxidant activity. The optimal growth medium is crucial for developing growth curves. Bioactive compounds were identified using Liquid Chromatography-Mass Spectrometry (LC-MS). Results indicated that explants grown on a medium combining picloram and kinetin exhibited better growth than those grown on a 2,4-D and kinetin combination. The callus colors varied from white to yellowish-white, yellow, and brownish-yellow, with a crumbly texture. Callus from all treatments contained bioactive compounds indicated by antioxidant activity, flavonoid content, and total phenolics. LC-MS analysis identified 87 types of secondary metabolite compounds. Callus treated with picloram and kinetin consistently produced flavonoids and phenolics and exhibited antioxidant activity.